ANALISIS PENGAKUAN PENDAPATAN PENJUALAN KONSINYASI DAN BIAYA PENJUALAN UNTUK AKUNTABILITAS LAPORAN KEUANGAN PADA PT BUMI AKSARA GROUP - Riri Oktaviani; Hayuningtyas Pramesti Dewi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
This study discusses the accounting for consignment sales and sales costs in PT Bumi Aksara Group. Data was obtained from PT Bumi Aksara Group in 2017. This study is a qualitative study in which the data is analyzed by comparing accounting standards that apply to consignment sales and sales costs with the reality that occurs in the company. The results of this study are that the company has not separated regular and consignment sales, ss for the charging of sales costs such as promotional costs, commission fees and expeditions are not recognized in the appropriate cost group. so financial reporting is not accountable.